An Interpretation of Two Personal Names in the Ninth Line of the Tonyukuk Inscription (Toñ S2) - Rykin, Pavel (JAOS, 2020)
The paper deals with the etymology of the personal names Qunï Säŋün and Toŋra Simä appearing in the ninth line of the Old Turkic Tonyukuk inscription (ca. 716). These names are borne by the envoys sent by the kagan of the Tokuz Oghuz to the Chinese and Khitan, respectively, to conclude a military alliance against the Turks. Both names have the same structure, a combination of an ethnonym (qun(ï) vs. toŋra), referring to a tribal unit within the Tiele 鐵勒 confederation, and a title of Chinese origin (säŋün vs. simä). Based on a thorough analysis of historical and philological data, the authors try to establish possible ethnolinguistic grounds for the Tokuz Oghuz mission, which have so far eluded researchers of the inscription and can be fully restored only in the light of the latest discoveries in the history and philology of Inner Asia of the Old Turkic period, e.g., the decipherment of the famous Khüis Tolgoi inscription from Mongolia.